Decision Tree Approach for Capital Expenditure Decision - a Tool for Effective Strategic Human Resource Management - Bhatt, Pushpa; T, Lakshmi (Ushus Journal of Business Management, 2021)
Strategic Human Resources Management aims at integrating strategic management with human resources management by aligning company objectives with people management systems.